Blockchain, an enabling technology for transparent and accountable decentralized public participatory GIS. (October 2020) - Farnaghi, Mahdi; Mansourian, Ali
Abstract: Web-based public participatory GIS (PPGIS) has been used by governmental organizations to facilitate people's contribution to decision-making processes. However, these applications do not provide an open and transparent environment for public participation. This study suggests that PPGISs should be developed as decentralized applications (DApp) based on Ethereum blockchain technology to have a fully open, transparent, and accountable environment for public participation. In a blockchain-based PPGIS, the collected data are securely saved on the blockchain. The validity of the data, replicated on the nodes of the peer-to-peer blockchain network, is ensured through a consensus process without any central control. The data is tamper-free and immutable. Additionally, the data is openly accessible to institutions and citizens. A prototype PPGIS was developed as a DApp through which users can participate in the site selection of urban facilities. Using the application, they compare and rank different criteria. The system solves an analytic hierarchy process to calculate the weights of the criteria. A suitability map is generated afterward and published to be used by both citizens and decision-makers. The feasibility of the application, along with the issues that need to be considered while using blockchain technology for urban planning and development, are thoroughly discussed. Highlights: An approach for developing Public Participatory GIS (PPGIS) as a decentralized application on blockchain was proposed It can effectively increase the openness, transparency, and accountability of the participatory planning processes A prototype system for participatory site selection in cities was developed The feasibility of the approach was demonstrated through a case study The opportunities and challenges of using blockchain technology for PPGIS applications were discussed